Implementation of an Internet of Things (IoT)-Based Water Level Early Warning System With Telegram Notification - Lengkong, Agnes Gratia; Salaki, Deiby Tineke; Alfonsius, Eric (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2025)
Water level is an important parameter in monitoring hydrological dynamics, particularly in drainage channels, as significant changes can trigger flooding and disrupt public activities, including in the Faculty of Mathematics and Natural Sciences (FMIPA) campus at Sam Ratulangi University. This study aims to design and implement an early warning system for water level based on the Internet of Things (IoT) that can provide real-time notifications via Telegram. The system utilizes the ESP32 microcontroller, HC-SR04 Ultrasonic Sensor, and Raindrop Sensor to detect rainfall and measure water levels in the drainage channel. The system is designed using the Waterfall model and tested with a black-box approach. Notifications are automatically sent to Telegram when the water level status reaches the "Alert" or "Overflow" category, and will stop once the status returns to "Safe." The test results show that the system functions accurately, the network connection is stable, and notifications are sent in a timely manner. This study contributes to local flood mitigation and enhances the preparedness of the academic community towards rising water levels.